Chapter Encyclopaedias and Commentaries - Markham, J. Geller (De Gruyter, 2015)
This paper looks at how empirical knowledge was assembled and interpreted in Babylonian academies and investigates two Neo-Assyrian plant lists: KADP 2 and KADP 4. These two lists are not simple collections of scholastic information but represent examples of theoretical botany and pharmacology. It is suggested that KADP 4 is a kind of proto-commentary, in which glosses represent key-words for hermeneutical elaborations. The paper concludes with an annotated transliteration and translation of KADP 4.